Art for Ages: The Effects of Group Music Making on the Wellbeing of Nursing Home Residents - Paolantonio, Paolo; Cavalli, Stefano; Biasutti, Michele; Pedrazzani, Carla; Williamon, Aaron (Frontiers in Psychology, 2020)
In many countries, life expectancy has increased considerably in past years, and the importance of finding ways to ensure good levels of wellbeing through ageing has become more important than ever. Arts based interventions are promising in this respect, and the literature suggests that musical activities can reduce isolation and anxiety and foster feelings of achievement and self-confidence. The present study examined the effects of group music making programmes on the health and wellbeing of nursing home residents in Southern Switzerland. A team of professional and student musicians delivered 10 weekly music sessions in four nursing homes, focusing on singing, rhythm-based activities with percussion instruments, and listening to short, live performances. 22 participants (16 women, aged 72-95 years, mean 83.6, SD ± 6.9) were recruited to take part in the study and were interviewed after the last music session. The data were analyzed with thematic analysis to investigate how residents experienced group music making and its effects. The findings show that the music programmes were beneficial for residents’ wellbeing. Music plays an important role in their lives, both in their pasts and presently, and being involved in musical activities offers engagement and novelty in daily life, providing learning opportunities and facilitating interpersonal relationships. Moreover, these results were due to direct interactions with the musicians involved. Residents particularly appreciated the opportunity to listen to live performances as part of the sessions. This study suggests that nursing home residents value music and that music based interventions play an important and direct role in enhancing their wellbeing.